KINEMATIC ANALYSIS OF SWIMMING TECHNIQUE BASED ON SYNCHRONOUS VIDEO RECORDING OF LINEAR MOTION - Ponimasov, O.E.; Pugachev, I.Yu.; Paramzin, V.B.; Raznovskaya, S.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to evaluate and select swimming technique models that are most adequate to the swimmer's individual motor predisposition based on the measurement of hydrodynamic parameters and synchronous video recording of linear movement. Methods and structure of the study. The application of methods for fixing the kinematic and dynamic structures of the swimmer's movements is considered on the example of the swimming technique of the test swimmer-master of sports, specializing in freestyle swimming for medium distances. The registration of variables was carried out by means of synchronous video recording of the swimmer's underwater movements during linear swimming. Results and conclusions. As a result of comparison of various technical variants of arm stroke in front crawl swimming, the possibility of using methods of fixing the kinematic and dynamic structures of stroke movements for an individual choice of a swimming technique model, the most adequate individual motor predisposition of the swimmer, has been established. As a personal effective technical option for swimming, an extended arm stroke along an S-shaped trajectory to the hips with the following statistical indicators is proposed: positive inertia force - 275 N; force of negative inertia - 146 N; average speed - 1.64 m/s; standard deviation - 0.12; coefficient of variation - 6.6%; efficiency of swimming technique - 75.4%.